UPAYA MENURUNKAN HIPERTENSI PADA MASYARAKAT DENGAN SENAM ANTI STROKE DI DSN. MENCON, DS. TAWUN, KEC. KASREMAN, KAB. NGAWI WILAYAH KERJA PUSKESMAS KASREMAN KABUPATEN NGAWI - Sa'adah, Hamidatus Daris (JPKM: Jurnal Profesi Kesehatan Masyarakat, 2021)
UPAYA MENURUNKAN HIPERTENSI PADA MASYARAKAT DENGAN SENAM ANTI STROKE DI DSN. MENCON, DS. TAWUN, KEC. KASREMAN, KAB. NGAWI WILAYAH KERJA PUSKESMAS KASREMAN KABUPATEN NGAWI  Hamidatus Daris Sa’adah 1*, Yudisa Diaz Lutfi 2, Rini Komalawati3 1,2,3 Akademi Keperawatan Pemerintah Kabupaten Ngawi*Korespondensi:hamy.daries@gmail.com ABSTRACT Background: That many hypertensive patients with uncontrolled blood pressure and the number continues to increase. Residents in etc. Kiss, etc. Wasps especially with hypertension is rarely checked into a health center if you experience complaints, such as the head feels heavy or dizzy. Residents said they had never done blood pressure checks routinely as a form of control or alertness to their hypertension. Only occasionally follow the elderly exercise programmed from the Puskesmas. Prevention and control efforts can be done, among others, with a diet low in salt and low fat, stop smoking and alcohol, exercise, get enough rest, and avoid stress. Early detection by routine blood pressure checks is also important to be able to provide treatment faster so that no worse complications occur. Objectives: Increase knowledge, detect awareness of hypertension, and the willingness of groups at risk and hypertension sufferers can control hypertension. Methods: Community service, namely anti-stroke gymnastics and blood pressure measurement checks, questions and answers, and discussions about the introduction and follow-up of hypertension in the community setting. Results: The majority of people involved in community service were women (70%) with blood pressure more than 140/90 mmHg. Most of the health counseling participants did joint anti-stroke exercises. Conclusion: Community service activities that have been carried out include inspection activities to recognize and detect hypertension early, about how to check blood pressure and control hypertension with anti-stroke exercises in residents of Mencon Hamlet, Tawun Village, Kasreman District. In addition, the activities carried out in this community service are health checks. Health examination (examination of blood sugar, uric acid, and cholesterol). This is given to patients or families of hypertension sufferers and the general public. especially. Some residents have been present according to the target so that the goal in increasing the role of the community, especially families in early detection and control of hypertension in Mencon Hamlet, Tawun Village, Kasreman District.